Trends In The Development Of Modern Cinema Art (Eurasian Journal of Engineering and Technology, 2026)
The article presents the contemporary trends in the development of cinema art and provides their socio-philosophical analysis. It examines the digitization of the film production process, the increased accessibility of modern technologies, and offers reflections on the outcomes of these changes.